Luteal phase support with human chorionic gonadotropin in assisted reproductive technology. (July 2013) - Lewis, Erin I; Cook, Heather; DeCherney, Alan H
The luteal phase is a critical component in supporting early pregnancy by forming the corpus luteum, and priming the endometrium for implantation following conception. Unfortunately, in assisted reproductive technology, ovarian stimulation protocols disrupt the hormonal milieu of the menstrual cycle, resulting in a largely defective luteal phase. For the last three decades, the optimum regimen for luteal phase support in assisted reproductive technology has been explored. Human chorionic gonadotropin was one of the first agents utilized to rescue the corpus luteum, given its high affinity for luteinizing hormone receptor. In this article, the author will summarize the role of human chorionic gonadotropin for luteal support in improving reproductive outcomes.